On the Multilinear Singular Integrals and Commutators in the Weighted Amalgam Spaces. (4th May 2014) - Liu, Feng; Wu, Huoxiong; Zhang, Daiqing
Abstract : This paper is concerned with the norm estimates for the multilinear singular integral operators and their commutators formed by BMO functions on the weighted amalgam spaces L v w → q, L p α ℝ n . Some criterions of boundedness for such operators in L v w → q, L p α ℝ n are given. As applications, the norm inequalities for the multilinear Calderón-Zygmund operators and multilinear singular integrals with nonsmooth kernels as well as the corresponding commutators on L v w → q, L p α ℝ n are obtained.